Pembinaan Potensi Wirausaha Dalam Pengelolaan Usaha Angringan - Syamlan, Adiba Fuad; Suharto, Suharto; Rusdiyanto, Rusdiyanto; Hasanah, Anisaul; Ulum, Bustanul; Tuharea, Firdaus Indrajaya (Universitas Negeri Gorontalo, 2024)
Service activities are carried out based on the obstacles faced by a business actor, which reflects the inconsistency of business activities that have an impact on services that can be categorized as not good. This business activity has indications of poor management, and this is an essential need for business activities which cannot be separated from the importance of understanding financial management. To be precise, in this activity, business income or results that did not meet expectations were found. Through this activity, it is known that there are obstacles in financial management that affect workers' service to consumers and even the calculation of funding turnover or financing for the business. The aim and urgency of this service are to provide an understanding of the importance of commitment to financial recording so that it can become a benchmark and provide information on activities. Business the information in question is information that contains sustainable business activities. The stages of service implementation activities are divided into direct (face-to-face) and indirect (programmed arrival) implementation. The results of developing this simple recording concept are expected to provide new work patterns and new thinking for workers and business owners so that they can plan development activities that can be pursued.